Penerapan Sistem Neuro Associative Conditioning (NAC) pada Guru sebagai Upaya Meningkatkan Mutu Pendidikan - Iskandar Agung (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
A variety of educational and training programs for teachers have long been implemented by the government, but it has not given a significant effect in improving the quality of national education, especially in elementary and secondary education. In fact, even today there are many teachers who have obtained the certificate of an educator, the achievement of quality education tend has not been satisfied. That is because the awarding of educator certification not accompanied by any change in the teacher in carrying out his/her main task. In carrying their tasks, teachers are still stuck, survive, and guided by the old valuesÂ Â that tended to be passive. They are just running errands, in one direction teaching, boring, poor creativity, dependence, and others a like. Instead, teachers have not been able to transform themselves in accordance with the demands of competence and work professionalism, which is marked by attitudes and behavior of active learning, achievement-oriented, creative, doing self-development constantly, and so forth. Explicitly, that the effort to improve the quality of education will be difficult to achieve if it is not accompanied by a change in mind set or way of thinking within teacher. Adoption of NAC conception system as a way to change mind set or way of thinking seems noteworthy and need to be applied to teachers. Through that changes, it is expected to be the driving energy for teachers in carrying their task/ job competently and professionally.ABSTRAKÂ Kajian ini bertujuan untuk membahas keberlangsungan perubahan dalam diri guru, terutama terkait dengan cara berpikir sejalan dengan tuntutan profesionalisme kerja. Hasil kajian menunjukkan bahwa secara eksplisit, bahwa upaya peningkatan mutu pendidikan tergantung dari sikap dan perilaku profesionalisme kerja guru. Berbagai perlakuan untuk meningkatkan kemampuan dan keterampilan guru mengajar melalui penilaian portofolio dan pendidikan pelatihan profesionalisme guru (PLPG) melalui Lembaga Pendidikan dan Tenaga Kependidikan (LPTK) mengindikasikan masih banyak guru yang telah memperoleh sertifikat pendidik, namun pencapaian mutu pendidikan cenderung masih belum memuaskan. Guru masih terjebak, bertahan, dan berpedoman pada nilai-nilai lama yang cenderung pasif, sekedar menjalankan tugas, pembelajaran searah, membosankan, kurang kreatif, ketergantungan, dan lain sebagainya. Sebaliknya, guru belum mampu mengubah diri sesuai tuntutan kompetensi dan profesionalisme kerja, sikap dan perilaku pembelajaran aktif, berorientasi pada prestasi, interaktif, kreatif, dan melakukan pengembangan diri. Hal ini sulit terwujud apabila tidak disertai dengan perubahan cara berpikir (mind set) diri guru. Pengadopsian konsepsi sistem Neuro Associative Conditioning (NAC) sebagai upaya perubahan cara berpikir, kiranya patut diperhatikan dan diterapkan terhadap guru.